2012
DOI: 10.1042/bj20112119
|View full text |Cite
|
Sign up to set email alerts
|

Force-induced apoptosis mediated by the Rac/Pak/p38 signalling pathway is regulated by filamin A

Abstract: Cells in mechanically challenged environments cope with high-amplitude exogenous forces that can lead to cell death, but the mechanisms that mediate force-induced apoptosis and the identity of mechanoprotective cellular factors are not defined. We assessed apoptosis in NIH 3T3 and HEK (human embryonic kidney)-293 cells exposed to tensile forces applied through β1-integrins. Apoptosis was mediated by Rac-dependent activation of p38α. Depletion of Pak1 (p21-activated kinase 1), a downstream effector of Rac, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…In vascular endothelial cells Pak2 was suggested to be a proinflammatory factor in atherogenesis through its matrix-specific activation of JNK and NF-kB and resulting increase in vascular permeability in response to shear (Funk et al, 2010;Iliev et al, 2009;Orr et al, 2007;Orr et al, 2008). Pak1 mediated actin cytoskeleton reorganization in sheared pulmonary endothelial cells (Birukov et al, 2002) and apoptosis in response to tensile forces in NIH3T3 and HEK cells (Shifrin et al, 2012). The role of Pak1 in the MC response to stretch and in matrix upregulation remain undefined and are addressed by our studies.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In vascular endothelial cells Pak2 was suggested to be a proinflammatory factor in atherogenesis through its matrix-specific activation of JNK and NF-kB and resulting increase in vascular permeability in response to shear (Funk et al, 2010;Iliev et al, 2009;Orr et al, 2007;Orr et al, 2008). Pak1 mediated actin cytoskeleton reorganization in sheared pulmonary endothelial cells (Birukov et al, 2002) and apoptosis in response to tensile forces in NIH3T3 and HEK cells (Shifrin et al, 2012). The role of Pak1 in the MC response to stretch and in matrix upregulation remain undefined and are addressed by our studies.…”
Section: Introductionmentioning
confidence: 77%
“…No studies have examined the role of Pak1 in MC, but Pak isoforms were shown to be activated in response to mechanical signals (Iliev et al, 2009;Shifrin et al, 2012). In vascular endothelial cells Pak2 was suggested to be a proinflammatory factor in atherogenesis through its matrix-specific activation of JNK and NF-kB and resulting increase in vascular permeability in response to shear (Funk et al, 2010;Iliev et al, 2009;Orr et al, 2007;Orr et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More recent data indicate that FLNa is required for β1 integrin activation at the outset of cell spreading on collagen, possibly by promoting the trafficking and cell surface expression of β1 integrin (23, 24). Notably, we found that FLNa is involved in the prevention of forced‐induced apoptosis through the Rac/Pak/p38 signaling pathway (25) and may play a mechanoprotective role in response to applied tensile forces.…”
mentioning
confidence: 99%
“…38,59 P38 signaling is also important for luminal epithelial cell apoptosis and P38 is a well-known target of Rac1 molecule. 41,[60][61][62] Nonetheless, it is conceivable that a tightly regulated TNFα-Rac1-P38 signaling cascade is essential for uterine luminal epithelium clearance during postimplantation uterine development.…”
Section: Discussionmentioning
confidence: 99%